Charged particle optics theory an introduction - Groves, Timothy R. (Optical sciences and applications of light, 2015)
Charged Particle Optics Theory: An Introduction identifies the most important concepts of charged particle optics theory, and derives each mathematically from the first principles of physics. Assuming an advanced undergraduate-level understanding of calculus, this book follows a logical progression, with each concept building upon the preceding one.